THE INFLUENCE OF MULTIMEDIA ON LEANING OUTCOME IN SOCIAL STUDIES SUBJECT OF THE GRADE V STUDENTS AT SD INPRES GUNUNG SARI - Nurul Kami Sani; Rizal Rizal; Ni Luh Sri Rahayu (Universitas Tadulako, 2020)
This study aims to determine the effect of multimedia on the learning outcomes of fifth grade students in social studies learning at SD Inpres Gunung Sari. The method used in this study is the pre-experiment method with one group research design pre test post test design. The study was conducted on fifth grade students at Gunung Sari Inpres Elementary School in the 2019/2020 study year. The sampling technique is done by saturated sampling. Data collection was carried out using the initial test instrument and the final test to find out the improvement of student learning outcomes after the learning media was applied during the learning process as well as a questionnaire to find out student responses regarding the use of multimedia in the learning process. The results showed that the average score of a student's initial test was 68.09 and the average score of a student's final test was 90.47, which showed an increase before and after learning by using multimedia. In addition, the effect of multimedia on student learning outcomes can be seen from the hypothesis test which shows that the results of t arithmetic greater than t table that is equal to 6.669> 2.086. Because it is known t arithmetic> from t table then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So from this study it can be concluded that there is an influence of the use of multimedia on the learning outcomes of Social Studies grade V SD Inpres Gunung Sari.